I'm in Love with My Car Psychological Attachment to Cars, Automated Vehicles and the Driverless Future. (1st January 2022) - Barreto, Raul; Kellett, Jon; Pierce, Joshua; Van den Hengel, Anton
We investigate how non-utilitarian car preferences and current perceptions of automated vehicles (AVs) affect commuters' openness to driverless car technology and perceptions of the driverless future. We identify four latent composite factors representing otherwise directly unobservable preference structures: psychological attachment to conventional cars; objective preference for traditional automotive safety; openness to perceived attributes of AVs; and willingness to embrace versus actively resist the driverless future. Conditional on commuters' psychological attachment to cars and their current perception of AVs, we investigate commuters' willingness to relinquish their traditional car in the hypothetical future to better understand the implications of future policy challenges.